A systematic review of psychological training or interventions given to UK military personnel prior to deployment. Issue 1 (27th October 2020) - Harden, Larissa; Jones, N; Whelan, C; Phillips, A; Simms, A; Greenberg, N
Abstract : Introduction: Predeployment stress management/mental health training is routinely delivered in an effort to mitigate potential adverse psychological effects. Little is known about the effectiveness of such interventions. Methods: A systematic literature review explored research outcomes related to this subject, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guidelines. An electronic database search using key terms identified studies published between January 2007 and March 2019. Comprehensive inclusion/exclusion criteria were applied and study quality was appraised by two reviewers using 12 criteria adapted from the Critical Appraisal Skills Programme (CASP) checklist. Papers were excluded if they were allocated CASP scores ≤10 out of 24. Results: 2003 references were identified; 15 papers fulfilled inclusion criteria and quality threshold requirements. Included studies were randomised controlled trial design (n=8), quasi-experimental (n=5), case report (n=1) and cross-sectional (n=1). Duration of follow-up assessment varied from immediately postintervention to 24 months. The included studies were heterogeneous so clear recommendations relating to predeployment training for military personnel could not be made. Although somewhat disparate, predeployment interventions shared the aim of promoting prior to, during and after deployment health and well-being. Social benefits such as improved cohesion and improved stress management skills were identified in some studies, although substantial mental health and well-being benefits were not found. Conclusions: Evidence for the effectiveness of predeployment psychological interventions is scant. Every attempt should be made to use methods and measures to facilitate comparisons across studies, to attempt a longer follow-up timescale and to clarify key trainer characteristics.